From Data to Action: A Qualitative Study of Rapor Pendidikan-Based Planning in Indonesian Primary Schools - Desi Rahmawati; Nurhattati Nurhattati; Ujang Suherman; Dirgantara Wicaksono (STAI Hubbulwathan Duri, 2025)
Data-based educational planning has become a key policy direction in Indonesia through the implementation of the Education Report Card (Rapor Pendidikan). However, empirical evidence on how primary schools utilize this data for systematic planning remains limited. This study explores how public primary schools optimize the Education Report Card in educational planning processes. This study employed a qualitative multiple-case design involving 35 public primary schools in Pulogadung District, East Jakarta. Data were collected through semi-structured interviews with principals, vice principals, teachers, and school operators (n = 107), non-participant observations of planning activities, and analysis of school planning documents. The data were analyzed thematically using Miles and Huberman’s framework, supported by cross-case comparison to identify planning typologies and optimization levels. The findings revealed two dominant planning typologies: strategic and reactive. Most schools demonstrated a strategic orientation characterized by systematic data analysis, long- and medium-term planning, and high stakeholder involvement. Schools with higher levels of data literacy and collaborative engagement were more effective in translating Education Report Card data into targeted programs, particularly in literacy and numeracy improvement. In contrast, reactive schools tended to rely on short-term responses and showed limited integration of data into sustainable planning. The study highlights that effective use of the Education Report Card is mediated by data literacy and stakeholder participation. Strengthening these capacities is essential for transforming educational data into actionable and sustainable school improvement strategies.